Identification of buried lunar impact craters from GRAIL data and implications for the nearside maria. Issue 6 (24th March 2016) - Evans, Alexander J.; Soderblom, Jason M.; Andrews‐Hanna, Jeffrey C.; Solomon, Sean C.; Zuber, Maria T.
Abstract: Gravity observations from the dual Gravity Recovery and Interior Laboratory (GRAIL) spacecraft have revealed more than 100 quasi‐circular mass anomalies, 26–300 km in diameter, on the lunar nearside. These anomalies are interpreted to be impact craters filled primarily by mare deposits, and their characteristics are consistent with those of impact structures that formed prior to, and during, intervals of flooding of feldspathic terrane by mare basalt lavas. We determine that mare deposits have an average density contrast of 850 − 200 + 300 kg m −3 relative to the surrounding crust. The presence of a large population of volcanically buried craters with minimal topographic expression and diameters up to 300 km requires an average nearside mare thickness of at least 1.5 km and local lenses of mare basalt as thick as 7 km. Key Points: One‐hundred four buried crater candidates on the lunar nearside are identified from gravity anomalies The density, thickness, and volume of infilling deposits are determined